1998
DOI: 10.1080/00071669888944
|View full text |Cite
|
Sign up to set email alerts
|

Yolk and serum cholesterol and production traits, as affected by incorporatinga supraoptimal amount of copper in the diet of the leghorn hen

Abstract: 1. An experiment was conducted to investigate the possibility of lowering the yolk cholesterol of the egg by supplementing the diet with supraoptimal amounts of copper (50, 150 or 250 mg/kg) as sulphate or acetate. 2. A significant reduction in egg production and a negative effect on food conversion was found when 250 mg/kg of copper was added compared to the control (no added copper). Acetate seemed significantly less harmful in both cases. 3. A significant linear reduction was found in plasma and yolk choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 12 publications
0
14
2
2
Order By: Relevance
“…The results of cholesterol and triglyceride ratios of egg and serum were supported by Kaya and Macit 21 who founded that the supplementation of 200 ppm copper did not have a significant effect on cholesterol and triglyceride ratios of egg and serum. On the contrary to the result of this experiment, in previous studies, egg yolk cholesterol in laying hens was decreased by dietary Cu supplementation [5,13,40,41] . Also Abaza et al [42] stated that Cu supplementation at 0 to 100 and 200 mg/kg levels in the laying quail diets decreased cholesterol and triglyceride concentrations of serum.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The results of cholesterol and triglyceride ratios of egg and serum were supported by Kaya and Macit 21 who founded that the supplementation of 200 ppm copper did not have a significant effect on cholesterol and triglyceride ratios of egg and serum. On the contrary to the result of this experiment, in previous studies, egg yolk cholesterol in laying hens was decreased by dietary Cu supplementation [5,13,40,41] . Also Abaza et al [42] stated that Cu supplementation at 0 to 100 and 200 mg/kg levels in the laying quail diets decreased cholesterol and triglyceride concentrations of serum.…”
Section: Discussioncontrasting
confidence: 54%
“…Nutritionist have been able to alter the diet of laying hens so that their eggs contain less cholesterol than the standard eggs. Results obtained from different studies have successfully demonstrated that natural products [4] and copper [5] could offer solutions to the health problem and cholesterol reduction. Natural products, essential extracts or oil derived from herbs and spices, exhibit hypocholesterolemic effect [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Estimated Haugh units showing the albumen quality (Menezes et al, 2012) were slightly higher in eggs from hens supplemented with copper. Through studies of Ankari et al (1998) conducted on copper's influence on organisms and productivity of hens, the hens were supplemented with copper, 250 ppm Cu, in a form of sulphate, protein compound, and lysine chelate. Compared to the control group, protein intake was lower in groups 2 and 3, but the group treated with lysine chelate did not show any difference in comparison to the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Bakalli et al (1995) observaram que altas concentrações de cobre, como sulfato de cobre pentahidratado, em dietas para frangos reduziram a concentração da enzima glutationa hepática e a atividade da HMG-CoA redutase, diminuindo a síntese de colesterol tecidual. A redução de colesterol no sangue (20%) e na gema de ovos (14%) também foi observada por Al Ankari et al (1998), ao utilizarem 250 mg de sulfato e acetato de cobre nas rações. De acordo com Valsala & Kurup (1987) e Kim et al (1992), citados por Al Ankari et al (1998), a enzima glutationa é conhecida por regular a biossíntese de colesterol e estimular a HMG-CoA redutase.…”
Section: Introductionunclassified
“…A redução de colesterol no sangue (20%) e na gema de ovos (14%) também foi observada por Al Ankari et al (1998), ao utilizarem 250 mg de sulfato e acetato de cobre nas rações. De acordo com Valsala & Kurup (1987) e Kim et al (1992), citados por Al Ankari et al (1998), a enzima glutationa é conhecida por regular a biossíntese de colesterol e estimular a HMG-CoA redutase.…”
Section: Introductionunclassified